HELLP SYNDROME BENIGN OUTCOME CASE REPORT - T. V. Karpenko; T. L. Smirnova (Акушерство, гинекология и репродукция)
The condition of the patient with 32 week pregnancy associated with complicated with preeclampsia and HELLP syndrome severe gestosis pathogenetically based therapy was worsening as severe gestosis symptoms remained, proteinuria increased to 2,1 gram per liter, thrombocytes slided to113х109/l. After cesarean section carried out in critical condition the condition of the patient worsened: during first 24 hours of postsurgery ALT was 792 u/l, AST was 1165 u/l, by the end of the second 24 hours D-dimer made up 3222 ng/ml, ferment content decreased(ALT 545 u/l, AST 341u/l). In the clinical HELLP syndrome course as high levels of D-dimer as 6086 ng/ml during the third 24 hours, during the fifth 24 hours-4392 ng/ml were marked. Early diagnostics and timely surgery, pathogenetically based gestosis heparin therapy insured favourable outcome of the HELLP syndrome of the patient.